Allowing access to parents/caregivers into COVID-19 hospitalization areas does not increase infections among health personnel in a pediatric hospital - De la Rosa-Zamboni, Daniela; Adame-Vivanco, María José; Luque-Coqui, Mercedes; Jaramillo-Esparza, Carlos Mauricio; Ortega-Riosvelasco, Fernando; Reyna-Trinidad, Irineo; Guerrero-Díaz, Ana Carmen; Ortega-Ruiz, Sergio Gabriel; Saldívar-Salazar, Sergio; Villa-Guillen, Mónica; Nieto-Zermeño, Jaime; Bonilla-Pellegrini, Sergio René; et al. (Frontiers in Pediatrics, 2022)
Background: At the beginning of the current COVID-19 pandemic, it became critical to isolate all infected patients, regardless of their age. Isolating children has a negative effect on both, them and their parents/caregivers. Nevertheless isolation was mandatory because of the potential risk that visitation might have on COVID-19 dissemination mostly among health personnel. Methods: From the starting of the COVID-19 pandemic in our pediatric hospital visits were forbidden. This two months period (April-May) was called P1. In June parents were allowed to visit (P2), under a visiting protocol previously published. Hospital workers were monitored for the presence of COVID-19 symptoms and tested for the infection when clinically justified. The positivity proportion and the relative risk (RR) of COVID-19 among the health personnel between periods were calculated. The caregivers were also followed up by phone calls. Results: Since April 2020 to November 2020, 2,884 health personnel were studied for 234 days, (318,146 workers days). Although the COVID-19/1000 health personnel days rate decreased from one period to another (1.43 vs 1.23), no statistically significant differences were found. During P1, 16 patients with COVID-19 were treated. During the follow up none of the family members were infected/symptomatic in P1, while in P2, 6/129 (4.65%) were symptomatic or had a positive test. All of them initiated between 2 and 4 days after the patient’s admission. As they also had some other infected family members it was not possible to ensure the source of infection. There were no statistically significant differences in the RR of COVID-19 in health personnel, (RR 1, 95% IC 0.69-1.06, p= 0.162). Conclusions: When safely implemented, allowing parents/caregivers to spend time with their hospitalized COVID-19 children does not increase the contagion risk for hospital workers or among themselves.